Physical Quality Test And Antibacterial Activity Of Anti-Acne Cream Preparation Of Neem Leaf Extract (Azadirachta Indica A.Juss) Against Propionibacterium Acnes - Fitriyana Fitriyana; Anna Fitriawati; Annie Rahmatillah (CV. AFDIFAL MAJU BERKAH, 2026)
Acne is a common skin disease caused by Propionibacterium acnes bacterial infection. Neem leaves (Azadirachta indica A.Juss) are known to contain active compounds such as azadirachtin, nimbin, nimbidin, and quercetin, which have antibacterial properties. This study aims to formulate neem leaf extract into a cream preparation, test its physical quality, and determine its antibacterial activity against Propionibacterium acnes. The research method used is a laboratory experiment. Neem leaf extraction was carried out by maceration method using 96% ethanol solvent. Cream preparations were made in four variations of extract concentration, namely 30%, 35%, 40%, and 45%. Physical quality tests of the preparations included organoleptic tests, homogeneity, pH, viscosity, and spreadability. Antibacterial activity tests were carried out using the diffusion method. The results showed that all cream formulas met the standards for good physical quality preparations. The results of the pH, viscosity, and spreadability tests met the requirements. The antibacterial activity of the cream preparation against Propionibacterium acnes was classified as strong, with an average inhibition zone of 28.94 mm at a 30% concentration, 19.78 mm at a 35% concentration, 33.93 mm at a 40% concentration, and 36.77 mm at a 45% concentration. The conclusion of this study is that neem leaf extract can be formulated into a cream preparation that meets physical quality standards and is effective in inhibiting the growth of Propionibacterium acnes bacteria.